Reading medieval literature in French lessons: a utopia ? - Burg, Gaëlle (Swiss Journal of Educational Research, 2021)
The literature traditionally used in secondary and higher education of French as a foreign language most often comes from the literature of the 19th, 20th and 21st centuries and less often from the works of the 16th, 17th and 18th centuries. But what about older texts from the Middle Ages? The data shows that they are completely ignored. Our article aims to defend the interest in teaching medieval literature in French as a foreign language and to support teachers. The aim is to provide effective activity tracks that allow learners to overcome the difficulties of authentic literature reading. For this, we base our approach on «global approach to written texts» (Moirand) and «interactive reading» (Cicurel) methodologies.